Preparative Mass Spectrometry Using a Rotating‐Wall Mass Analyzer. (19th March 2020) - Su, Pei; Hu, Hang; Unsihuay, Daisy; Zhang, Di; Dainese, Tiziano; Diaz, Rosa E.; Lee, Jongsu; Gunaratne, Don K.; Wang, Haiyan; Maran, Flavio; Mei, Jianguo; Laskin, Julia
Abstract: The design of functional interfaces is central to both fundamental and applied research in materials science and energy technology. We introduce a new, broadly applicable technique for the precisely controlled high‐throughput preparation of well‐defined interfaces containing polyatomic species ranging from small ions to nanocrystals and large protein complexes. The mass‐dispersive deposition of ions onto surfaces is achieved using a rotating‐wall mass analyzer, a compact device which enables the separation of ions using low voltages and has a theoretically unlimited mass range. We demonstrate an efficient deposition of singly charged Au144 (SC4 H9 )60 ions (33.7 kDa), which opens up exciting opportunities for the structural characterization of nanocrystals and their assemblies using transmission electron microscopy. Our approach also enables the high‐throughput deposition of mass‐selected ions from multicomponent mixtures, which is of interest to the controlled preparation of surface gradients and rapid screening of molecules in mixtures for a specific property. Abstract : Verdreht und verteilt : Präparative Massenspektrometrie mit einem Massenanalysator mit rotierenden Wänden ermöglicht die Abscheldung wohldefinierter polyatomarer Ionen von kleinen Molekülen bis zu Nanoclustern und Proteinkomplexen. Ebenfalls ermöglicht es die Hochdurchsatz‐Trennung und ‐Abscheidung von Molekülen aus Mehrkomponentenmischungen. Der Ansatz ermöglicht die Präparation funktioneller Grenzflächen und verwendet kostengünstige Instrumentierung.